Science Digital Library: Innovation in Improving Science Literacy of Elementary School Students - Prastiti, Maulidiya Rahma; Adi, Banu Setyo (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
The results of the initial study conducted at Sidoharjo 1 Elementary School found problems that caused the low science literacy of grade VI students. These problems include inappropriate teaching materials, less contextualized science learning, inadequate science learning media, and a lack of motivation for students to learn science. The purpose of this research is to develop a Science Digital Library that can improve science literacy. The method used in this research is the research and development of the ADDIE model with the stages of Analyze, Design, Develop, Implement, and Evaluate. The research subjects were 21 sixth-grade students of Sidoharjo 1 Elementary School. Data collection techniques are media and material expert validation, student response questionnaires, and tests. The results of the study were that media experts and material experts validated the Science Digital Library. The results of the media validation were 88% with very valid qualifications, while the material validation was 92% with very valid qualifications. Science literacy assessment instruments measure science literacy skills. The improvement was calculated by the normalized gain formula (g) with the result of 0.71. The result of this study is that the Science Digital Library is proven to be feasible and valid for use and can improve science literacy in grade VI students of Sidoharjo I Elementary School.